Managing relationships in qualitative impact evaluation to improve development outcomes: QuIP choreography as a case study - James Copestake; Claire Allan; Wilm van Bekkum; Moges Belay; Tefera Goshu; Peter Mvula; Fiona Remnant; Erin Thomas; Zenawi Zerahun (University of Bath, Centre for Development Studies (CDS), 2016)
Evaluation choreography - or who knows what when through the process of impact evaluation - has an important influence on the credibility and usefulness of findings. We explore such choreography from technical, political and ethical perspectives through reflection on a collaborative case study that entailed collaborative design of a qualitative impact evaluation protocol ('the QuIP') and its pilot use in Ethiopia and Malawi. Double blind interviewing was employed to reduce project specific confirmation bias, followed by staged 'unblinding' as a form of triangulation. We argue that these steps can enhance credibility of evidence and that ethical concerns associated with blinding can be addressed by being open with stakeholders about the process. The case study suggests qualitative impact evaluation can contribute to a more deliberative and less rigid style of international development practice.
Keywords: 330; Blinding; confirmation bias; impact evaluation; international development practice; qualitative methods